Effect and Mechanism of Catalpol on Behavior in Rats with Post-stroke Depression - WANG Xiangyu; ZHOU Xia; LIU Ju; LIU Fuhong; ZHANG Jiale; SUN Liping; LI Wanbin (康复学报)
ObjectiveTo explore the effect of catalpol on the behavior of post-stroke depression rats, and to explore its mechanism from the aspects of behavior, the expression of 5-hydroxytryptamine (5-HT), norepinephrine (NE) and brain-derived neurotrophic factor (BDNF) in peripheral serum and brain tissue.MethodsA total of twenty-four SD rats were randomly divided into model group, catalpol intervention group and sham operation group, with 8 rats in each group. The rats model of post-stroke depression were established by middle cerebral artery occlusion (MCAO) combined with the chronic unpredictable mild stress (CUMS) to induce depression-like behavior. The modeling time was 7 days. After the end of modeling, the open field test was used on the 1st, 4th, and 7th day. The behavior of the rats was evaluated by elevated plus maze measurement. TTC staining was used to detect cerebral infarction volume. The serum and hippocampus levels of 5-HT, NE, and BDNF were measured by enzyme-linked immunosorbent assay.ResultsCompared with the model group, the number of crossing grid, the number of standing and the total distance moved were significantly increased on the 4th and 7th day after intervention in the open field test, and the differences were significant (P<0.05). In the elevated plus maze measurement, the OE% and OT% were significantly increased in the catalpol intervention group on the 4th and 7th day after intervention, and the differences were significant (P<0.05), indicating that the catalpol could significantly increase the spontaneous activity of rats and relieve depression-like behavior. TTC staining showed that the volume of cerebral infarction in the catalpol intervention group was significantly reduced compared with model group (P<0.05). In the ELISA experiment, compared with the model group, 5-HT and BDNF in the catalpol intervention group were significantly increased on the 4th and 7th day after intervention, and the difference was significant (P<0.05); there was no significant difference in NE content in the catalpol intervention group on the 4th and 7th day after intervention (P>0.05); compared with the model group, the hippocampal 5-HT and BDNF in the catalpol intervention group increased significantly (P<0.05); there was no significant difference in the content of NE in hippocampus between the catalpol intervention group and the model group (P>0.05), indicating that catalpol could increase 5-HT and BDNF levels in rats with post-stroke depression, but did not significantly improve NE.ConclusionCatalpol can improve post-stroke depression, promote the recovery of neurological function, regulate the function of central serotonin system and promote the secretion of BDNF.